2008
DOI: 10.1002/hep.22280
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐kilodalton Tat‐interacting protein suppresses tumor metastasis by inhibition of osteopontin transcription in human hepatocellular carcinoma†

Abstract: It has been previously demonstrated that the 30-kDa TatM alignant tumors are characterized by dysregulated growth control, overcoming of replicative senescence, evasion of apoptosis, tissue invasion and metastasis, and sustained angiogenesis. 1 Several growth factors and cytokines play pivotal roles in the regulation of proliferation, survival, adhesion, and migration of malignant cells. 2,3 Osteopontin (OPN), an extracellular matrix protein secreted by a wide variety of cancers, binds to ␣ v ␤ integrin and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
3
42
1
Order By: Relevance
“…9 Our recent studies showed that TIP30 inhibited tumor metastasis through suppressing the expression of OPN in human hepatocellular carcinoma. 16 The role of TIP30 in the development and progression of lung cancer has not been fully characterized. In the present study, TIP30 expression was examined by immunohistochemistry in 206 lung carcinoma tissues, including 197 non-small cell lung cancers (NSCLC) and 9 SCLCs, and adjacent non-tumor tissues, as well as 70 matched lymph node metastases using a high-density tissue microarray.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Our recent studies showed that TIP30 inhibited tumor metastasis through suppressing the expression of OPN in human hepatocellular carcinoma. 16 The role of TIP30 in the development and progression of lung cancer has not been fully characterized. In the present study, TIP30 expression was examined by immunohistochemistry in 206 lung carcinoma tissues, including 197 non-small cell lung cancers (NSCLC) and 9 SCLCs, and adjacent non-tumor tissues, as well as 70 matched lymph node metastases using a high-density tissue microarray.…”
mentioning
confidence: 99%
“…15 Recently TIP30 was found to interact with Ets-1 and inhibit osteopontin (OPN) transcription. 16 Recent studies have linked TIP30 to metastatic progression of several different cancer types. Introduction of TIP30 into v-SCLC cells suppressed metastasis in SCIDhu-L mice.…”
mentioning
confidence: 99%
“…Deletion of Rab5a in cells inhibits the transport of EGFR from early endosomes to lysosomes and consequently causes sustained EGFR signaling and delayed EGFR degradation (19). Despite its importance to endocytic transport, how Rab5a mediates downregulation of receptor signaling remains unclear.TIP30, also known as HTATIP2 or CC3 (20, 21), is a tumor suppressor that has been demonstrated to act as a transcription cofactor to repress transcription in the nucleus (22,23) and to localize at the nuclear envelope to block nuclear importing (24). However, TIP30 also localizes in the cytoplasm, where its function is not known (25-28).…”
mentioning
confidence: 99%
“…TIP30, also known as HTATIP2 or CC3 (20, 21), is a tumor suppressor that has been demonstrated to act as a transcription cofactor to repress transcription in the nucleus (22,23) and to localize at the nuclear envelope to block nuclear importing (24). However, TIP30 also localizes in the cytoplasm, where its function is not known (25-28).…”
mentioning
confidence: 99%
“…It is known to be upregulated by heat shock, stress, aging, certain viruses, and the cytokine TGF-β. The tumor-suppressive activity of TIP30 has been linked to the induction of apoptosis, possibly by blocking of nuclear pores (11), and the suppression of osteopontin (14), a proinflammatory cytokine that has been implicated in the generation of Th17 cells, important for the generation of cell-mediated immunity. Osteopontin has been shown to be upregulated in chronic active MS lesions and has been linked to the exacerbation of the animal model for MS known as EAE (15).…”
Section: Potential Role Of Tip30 In Ms Pathogenesismentioning
confidence: 99%